1981
DOI: 10.1159/000179394
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Release in Rats 1 and 5 Days after Hypophysectomy

Abstract: In the present experiments the effect of an intravenous glucose (0.5 g/kg body weight) and an intravenous glibenclamide (1 mg/kg body weight) injection on insulin release was studied in conscious rats shortly after hypophysectomy. 1 and 5 days after removal of the pituitary gland both the fasting blood glucose and the serum insulin concentrations were significantly lower when compared with control rats as was the insulin response to the stimulation by glucose or glibenclamide. In order to elucidate the contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…These findings might be interpreted as a reflection of reduced translational efficiency together with a blunted insulin response to glucose due to the lack of GH. Several studies have shown that the insulin response to glucose is delayed and/or reduced in hypox-rat-isolated islets (Parman 1975) or in hypox rats in vivo (Penhos et al 1971;Heinze et al 1981). In another study, the first and second phase of insulin secretion in the perfused pancreas of hypox rats have been found to be depressed (Curry and Bennett 1973).…”
Section: Discussionmentioning
confidence: 93%
“…These findings might be interpreted as a reflection of reduced translational efficiency together with a blunted insulin response to glucose due to the lack of GH. Several studies have shown that the insulin response to glucose is delayed and/or reduced in hypox-rat-isolated islets (Parman 1975) or in hypox rats in vivo (Penhos et al 1971;Heinze et al 1981). In another study, the first and second phase of insulin secretion in the perfused pancreas of hypox rats have been found to be depressed (Curry and Bennett 1973).…”
Section: Discussionmentioning
confidence: 93%
“…They were housed under controlled conditions with constant temperature (24-26 C), constant humidity (50-60%), and a 14-h light, 10 pellet food (Type R3, Ewos, Sodertalje, Sweden) ad libitum. This diet consisted of 21% protein, 52% carbohydrates (starch), 6% fat, 11% water, 3.5% fibers, and 6.5% minerals and salts.…”
Section: Animalsmentioning
confidence: 99%
“…Recent studies have indicated that insulin might be an important long term regulator of the glucose transport capacity of adipose tissue (8). The insulin levels are low in hypophysectomized animals (9)(10)(11). To investigate the role of insulin in the changes in glucose metabolism and hormone responsiveness of adipose tissue of hypophysectomized animals, we examined the effects of additional glucose in the drinking water or insulin treatment of hypophysectomized rats on the responsiveness of adipose tissue to insulin and GH.…”
mentioning
confidence: 99%
“…The concentration of insulin in the blood is increased relative to normal and relative to glucose concentrations in acromegalic patients (137, 378,402,673,694), in rats harboring GH-secreting tumors (518, 523, 642, 645), and in transgenic mice (845), pigs (664), or sheep (679) that overexpress GH. Conversely, insulin levels in blood are usually low in hypophysectomized animals (200,208,249,358,516,663,863). In GH-deficient humans, fasting insulin levels may be lower (28, 59), un-changed (546,734), or higher than normal (548,734), depending on the degree of obesity (733).…”
Section: Pancreatic Beta Ce/hmentioning
confidence: 99%